Photoluminescence Emission of Cu Doped ZnS Microstructures Synthesized by Thermal Evaporation - Nghia, Nguyen Van; Hung, Nguyen Duy (VNU Journal of Science: Mathematics - Physics; Vol 34 No 2DO - 10.25073/2588-1124/vnumap.4221, 2018)
Cu doped ZnS microstructures were prepared by the thermal evaporation method using ZnS powder and CuCl2.2H2O powder as precusor materials. The microstructures was characterized by using X-ray diffraction (XRD) analysis. The XRD studies indicated that there are two phases (ZnS and ZnO) at the undoped sample, but most of the samples are only having wurtzite (hexagonal) phase of ZnS after doping. The photoluminescence emission and photoluminescence excitation of ZnS and Cu2+ doped ZnS microstructures have been studied. The photoluminescence excitation spectra of ZnS microstructures is presented around 374 nm. By doping of Cu2+ ion, the absorption wavelength is shifted towards the lower wavelength being an evidence for an increasing band gap. The emission spectrum of pure ZnS has a green emission band centred at around 520 nm. By doping Cu2+ ion, the peak of the green band in the luminescence spectra were transferred to 516 nm and appeared a strong blue peak at 440 nm. The reasons of these will be discussed in this paper. Keywords ZnS:Cu2+ microstructures, photoluminescence, thermal evaporation References H. Hiramatsu, H. Ohta, M. Hirano, and H. Hosono, Heteroepitaxial growth of single-phase zinc blende ZnS films on transparent substrates by pulsed laser deposition under H2S atmosphere, Solid State Commun., 124 (2002) 411. [2] K. Ichino, K. Ueyama, H. Kariya, N. Suzuki, M. Kitagawa, and H. Kobayashi, Photoluminescence study of ZnS / ZnMgS single quantum wells, Appl. Phys. Lett., 74 (1999) 3486. [3] W. Jian, J. Zhuang, W. Yang, and Y. Bai, Improved photoluminescence of ZnS:Mn nanocrystals by microwave assisted growth of ZnS shell, J. Lumin., 126 (2007) 735. N.V. Nghia, N.D. Hung / VNU Journal of Science: Mathematics – Physics, Vol. 34, No. 2 (2018) 1-7 7 [4] W. Q. Peng, G. W. Cong, S. C. Qu, and Z. G. Wang, Synthesis and photoluminescence of ZnS:Cu nanoparticles, Opt. Mater. (Amst)., 29 (2006) 313. [5] L. Wanjari, D. P. Bisen, N. Brahme, I. Prasad Sahu, and R. Sharma, Effect of capping agent concentration on thermoluminescence and photoluminescence of copper-doped zinc sulfide nanoparticles, Luminescence, 30 (2015) 655. [6] R. K. Tamrakar, UV-irradiated thermoluminescence studies of bulk CdS with trap parameter, Res. Chem. Intermed., 41 (2015) 43. [7] D. Li, B. L. Clark, D. A. Keszler, P. Keir, and J. F. Wager, Color control in sulfide phosphors: Turning up the light for electroluminescent displays, Chem. Mater., 12 (2000) 268. [8] J. Bang, B. Abrams, B. Wagner, and P. H. Holloway, Effects of coatings on temporal cathodoluminescence quenching in ZnS:Ag,Cl phosphors, J. Appl. Phys., 95 (2004) 7873. [9] P. D. Rack and P. H. Holloway, The structure, device physics, and material properties of thin film electroluminescent displays, Mater. Sci. Eng. R Reports, 21 (1998) 171. [10] L. Luo, H. Chen, L. Zhang, K. Xu, and Y. Lv, A cataluminescence gas sensor for carbon tetrachloride based on nanosized ZnS, Anal. Chim. Acta, 635 (2009) 183. [11] B. Dong, L. Cao, G. Su, W. Liu, H. Qu, and D. Jiang, Synthesis and characterization of the water-soluble silicacoated ZnS:Mn nanoparticles as fluorescent sensor for Cu2+ ions, J. Colloid Interface Sci., 339 (2009) 78. [12] N. Üzar, S. Okur, and M. Ç. Arikan, Investigation of humidity sensing properties of ZnS nanowires synthesized by vapor liquid solid (VLS) technique, Sensors Actuators, A Phys., 167 (2011) 188. [13] H. Tang, B. J. Kwon, J. Kim, and J. Y. Park, Growth modes of ZnS nanostructures on the different substrates, J. Phys. Chem. C, 114 (2010) 21366. [14] A. Datta, S. K. Panda, and S. Chaudhuri, Phase transformation and optical properties of Cu-doped ZnS nanorods, J. Solid State Chem., 181 (2008) 2332. [15] S. Ummartyotin, N. Bunnak, J. Juntaro, M. Sain, and H. Manuspiya, Synthesis and luminescence properties of ZnS and metal (Mn, Cu)-doped-ZnS ceramic powder, Solid State Sci., 14 (2012) 299. [16] L. Y. Shang, D. Zhang, and B. Y. Liu, Influence of Cu ion implantation on the microstructure and cathodoluminescence of ZnS nanostructures, Phys. E Low-Dimensional Syst. Nanostructures, 81 (2016) 315. [17] J. Hu, G. Wang, C. Guo, D. Li, L. Zhang, and J. Zhao, Au-catalyst growth and photoluminescence of zinc-blende and wurtzite ZnS nanobelts via chemical vapor deposition, J. Lumin., 122–123 (2007) 172. [18] D. Q. Trung, N. Tu, N. D. Hung, and P. T. Huy, Probing the origin of green emission in 1D ZnS nanostructures, J. Lumin., 169 (2016) 165. [19] T. Mitsui, N. Yamamoto, T. Tadokoro, and S. Ohta, Cathodoluminescence image of defects and luminescence centers in ZnS/GaAs (100), J. Appl. Phys., 80 (1996) 6972. [20] G. H. Yue et al., Hydrothermal synthesis of single-crystal ZnS nanowires, Appl. Phys. A Mater. Sci. Process., 84 (2006) 409. [21] S. Wageh, Z. S. Ling, and X. Xu-Rong, Growth and optical properties of colloidal ZnS nanoparticles, J. Cryst. Growth, 255 (2003) 332. [22] A. Goudarzi et al., Low-Temperature Growth of Nanocrystalline Mn-Doped ZnS Thin Films Prepared by Chemical Bath Deposition and Optical Properties, Chem. Mater., 21 (2009) 2375. [23] W. W. G. Becker and A. A. J. Bard, Photoluminescence and photoinduced oxygen adsorption of colloidal zinc sulfide dispersions, J. Phys. Chem., 78712 (1983) 4888. [24] N. Xuan, Fabrication and Photoluminescence Properties of ZnS Nanoribbons and Nanowires, 52 (2008) 1530. [25] Y. Y. Bacherikov et al., Structural and optical properties of ZnS:Mn micro-p